Knowledge spillovers and geopolitical challenges in global supply chains - Niclas Poitiers; Kamil Sekut (Bruegel, 2024)
This paper explores the role of knowledge spillovers through global supply chains against the backdrop of increasing geopolitical tensions and protectionist policies. The research, part of the ReThinkGSC project, underscores the importance of the international research and development ecosystem in fostering innovation. This ecosystem provides benefits to all countries involved and is essential for tackling global challenges. However, we highlight the growing threats to knowledge dissemination posed by policies aimed at preserving national security and leading technological positions.These measures, intended to safeguard strategic interests, risk fragmenting supply chains and stifling global innovation if they are applied on a broad basis. We recommend that restrictions on knowledge flows be limited to narrowly defined strategic areas and that countries adopt strategies to enhance internal knowledge dissemination, diversify supply chains and foster international economic ties. We emphasise the need for careful policy design, avoiding broad protectionist measures, and suggests bolstering R&D through public grants and tax incentives, and by promoting private-public partnerships.
Keywords: 330